(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed to explore whether there are differences among students with and without written expression difficulty in Self-Regulation of Learning, and if there are differences among students with written expression difficulty in Self-Regulation according to the gender (male/ female). this study also aimed to explore if there are differences among students without written expression difficulty in Self-Regulation of Learning according to the gender ,too. The sample consisted of (164) students of the sixth grade in Tartous city. the tools included a written expression test to differentiate students who have difficulty in written expression and those who don’t have. the tools also included a questionnaire of Self-Regulation. The descriptive approach was used. Findings showed that there are differences among students with and without written expression difficulty in Self-Regulation of Learning; moreover, It showed that there are not differences among students with written expression difficulty in Self-Regulation of Learning according to the gender, finally it showed that there is not a difference among students without written expression difficulty in Self-Regulation Of Learning according to the gender, too.